Formal Verification of Rewards and Penalties Mechanism of FFG Attestations: Ethereum 2.0 Beacon Chain Case Study - Muhammad Rashid; Imran Rasool; Nazir Ahmad Zafar; Hamra Afzaal (IEEE Access, 2025)
Ethereum 2.0 stands out as a progressive decentralized blockchain platform, drawing attention for its security, scalability, and flexibility. Central to Ethereum 2.0 is the Beacon Chain, serving as the cornerstone managing validator rewards, penalties, attestations, and slashing mechanisms. Rewards and Penalties Mechanism (RPM) is of particular importance within the Beacon Chain as it includes validator balances based on their attestation behavior. Despite the critical role of RPM in maintaining the reliability and security of the Beacon Chain, the absence of formal verification work employing model checking is notable. Therefore, this research endeavors to fill this gap by employing a formal verification technique to assess the RPM’s behavior concerning Friendly Finality Gadget (FFG) attestations. Utilizing Process Meta Language (PROMELA), a formal model of the RPM is specified, encompassing safety and liveness properties crucial for its robust functioning. The properties, including invalid attestation, integrity, fairness, availability, failure to attest, and inactivity imposition, are formalized through Linear Temporal Logic (LTL). Subsequently, the formal model alongside the specified properties is subjected to verification using the SPIN model checker. The properties are analyzed with respect to verification time, states visited, and memory usage. The outcome of this research contributes to a rigorous analysis of the RPM’s behavior. This work not only enhances an understanding of Beacon Chain’s operational dynamics but also underscores the importance of formal verification in ensuring the reliability and security of blockchain protocols.